2015
DOI: 10.5902/2179769216632
|View full text |Cite
|
Sign up to set email alerts
|

A dinâmica da família frente à diálise peritoneal no domicílio

Abstract: RESUMO: Objetivo: descrever a dinâmica da família frente à necessidade de um de seus membros realizar diálise peritoneal no domicílio. Método: pesquisa qualitativa realizada em uma clínica renal no Sul do Brasil, de março a maio de 2012. Foram entrevistadas sete famílias em suas residências. Os dados foram submetidos à análise temática. Resultados: a investigação da dinâmica das famílias aponta para a participação desde o processo inicial do tratamento, sendo permeado pela ajuda entre os seus membros, pelas al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The denial or even the illusion that adherence to treatment is not necessary causes the users to see the health professionals a harsh and impossible behavior, and can be understood as hostile attitudes. 4,11,15 Another aspect identified that hinders the capacity building of care involving dialysis therapy corresponds to the lack of information during the brief period between diagnosis and treatment. The lack of knowledge related to this therapy, as well as the myths that are told to the users, may interfere with the learning of PD care, which is essential for home practice.…”
Section: Difficulties Of the Users In Learning The Training Processmentioning
confidence: 99%
“…The denial or even the illusion that adherence to treatment is not necessary causes the users to see the health professionals a harsh and impossible behavior, and can be understood as hostile attitudes. 4,11,15 Another aspect identified that hinders the capacity building of care involving dialysis therapy corresponds to the lack of information during the brief period between diagnosis and treatment. The lack of knowledge related to this therapy, as well as the myths that are told to the users, may interfere with the learning of PD care, which is essential for home practice.…”
Section: Difficulties Of the Users In Learning The Training Processmentioning
confidence: 99%
“…PD has gained preference as a choice for treatment, however, imposes on the family understanding, mastery of the technique and complex logistics organization to assume the development of the practice at home. [4][5] KT is the best option to provide quality of life to the patient, but beyond the necessary compatibility between donor and recipient, it brings to the patient and the health system barriers such as: economic limitations, lack of basic prophylaxis and mainly the shortage of organs for donation. 6 Thus, given the reality offered by PD and KT, hemodialysis (HD) appears as the most prevalent TRS in Brazil since 1950, when it was first implemented.…”
Section: Introductionmentioning
confidence: 99%